Praktik Terbaik Mitigasi Risiko pada Lembaga Keuangan Syariah: Analisis Studi Kasus Empat Institusi - Putra, Gilang Chaya (Maliki Interdisciplinary Journal, 2024)
The research aims to analyze risk mitigation implemented by sharia banking. The method used in this research is descriptive qualitative through analysis of literature studies. The research results show that Bank M, UJKS JR, BPRS S, and Bank RS have implemented various risk mitigation strategies to maintain the stability and sustainability of their operations. This strategy includes setting segment limits and certain conditions, binding guarantees, transferring risks, increasing employee competency, using risk tools, as well as regular monitoring of the market and risks that may arise.